2020
DOI: 10.1111/bcp.14189
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine intake increases muscle oxygen saturation during a maximal incremental exercise test

Abstract: Aims:The main mechanism behind caffeine's ergogenicity lies in its tendency to bind to adenosine receptors, although other mechanisms might be involved. The aim of this investigation was to analyse the effects of caffeine on muscle oxygen saturation during exercise of increasing intensity. Methods:Thirteen healthy and active individuals volunteered to participate in a randomized, double blind, placebo-controlled crossover trial. During 2 different trials, participants either ingested a placebo (cellulose) or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…The present results also agree with those obtained by Gutiérrez-Hellín et al [19] who reported 3 mg/kg caffeine to increase MFO in healthy active young men, as well as those reported by Dodd et al [37] who indicate that 5 mg/kg of caffeine improved VO 2max in naive caffeine consumers. The higher MFO, Fat max and VO 2max values recorded in the present work after caffeine ingestion may be explained by (i) an enhancement of fatty acid mobilization and oxidation, aided by an increase in the release of epinephrine, (ii) a blockage of the A 1 , A 2A , and A 2B adenosine receptors, thus promoting the release of acetylcholine and dopamine which dampens pain perception, blunts perceived exertion, and delays fatigue [16,[38][39][40], (iii) an increase in motor unit recruitment, which results in higher rates of muscular contraction and alertness [16], and/or (iv) an increase in muscle oxygen saturation that might facilitate the use of fat at moderate exercise intensities and lead to higher VO 2 values at maximal exercise intensity [18].…”
Section: Caffeine Ingestion Mfo Fat Max and Vo 2maxmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results also agree with those obtained by Gutiérrez-Hellín et al [19] who reported 3 mg/kg caffeine to increase MFO in healthy active young men, as well as those reported by Dodd et al [37] who indicate that 5 mg/kg of caffeine improved VO 2max in naive caffeine consumers. The higher MFO, Fat max and VO 2max values recorded in the present work after caffeine ingestion may be explained by (i) an enhancement of fatty acid mobilization and oxidation, aided by an increase in the release of epinephrine, (ii) a blockage of the A 1 , A 2A , and A 2B adenosine receptors, thus promoting the release of acetylcholine and dopamine which dampens pain perception, blunts perceived exertion, and delays fatigue [16,[38][39][40], (iii) an increase in motor unit recruitment, which results in higher rates of muscular contraction and alertness [16], and/or (iv) an increase in muscle oxygen saturation that might facilitate the use of fat at moderate exercise intensities and lead to higher VO 2 values at maximal exercise intensity [18].…”
Section: Caffeine Ingestion Mfo Fat Max and Vo 2maxmentioning
confidence: 99%
“…Interestingly, the urine caffeine concentration recorded in doping control tests, especially for athletes of endurance-based sports, has increased progressively since it was removed from the above list [14]. Certainly, low-to-moderate doses of caffeine (~3-9 mg/kg) [15] can increase endurance performance [16] via the induction of significant increases in VO 2max , peak pulmonary ventilation, and muscle oxygen saturation during submaximal workloads [17,18]. A recent study by Gutierrez-Hellín et al [19] also shows caffeine ingestion to increase the MFO in healthy subjects of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms of action include reduced pain and perceived exertion, the stimulation of the ventilatory response, and changes in the muscle milieu by the retention of potassium ions and increased release of calcium ions from the sarcoplasmic reticulum [7,12]. Emerging evidence suggests that caffeine may stimulate increases in blood flow and muscle tissue saturation via endothelial nitric oxide synthase activity [13,14]. Increases in blood flow and O 2 availability are reported to increase muscle function by enhancing the metabolic steady-state of muscle tissue during both upper and lower-extremity exercise performed until failure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The main physiological mechanism behind the performance-enhancing effect of caffeine on endurance exercise is associated to caffeine’s capacity to block A 1 , A 2a and A 2b adenosine receptors on the central nervous system [ 15 ], although other local effects have also been proposed as contributing mechanisms [ 16 , 17 ]. The blockade of adenosine receptors with caffeine intake, confirmed in both animals [ 18 ] and humans [ 19 ], is based on three different characteristics of caffeine when ingested orally: rapid absorption in the gut [ 20 ], its capacity to pass through all biological membranes, including the blood–brain barrier, due to its lipophilic nature [ 21 ] and its structural similarity to adenosine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%